2015
DOI: 10.1104/pp.15.00612
|View full text |Cite
|
Sign up to set email alerts
|

Knocking Down of Isoprene Emission Modifies the Lipid Matrix of Thylakoid Membranes and Influences the Chloroplast Ultrastructure in Poplar

Abstract: Isoprene is a small lipophilic molecule with important functions in plant protection against abiotic stresses. Here, we studied the lipid composition of thylakoid membranes and chloroplast ultrastructure in isoprene-emitting (IE) and nonisoprene-emitting (NE) poplar (Populus 3 canescens). We demonstrated that the total amount of monogalactosyldiacylglycerols, digalactosyldiacylglycerols, phospholipids, and fatty acids is reduced in chloroplasts when isoprene biosynthesis is blocked. A significantly lower amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 87 publications
(125 reference statements)
2
42
0
Order By: Relevance
“…The lower amount of protein members of the photosynthetic apparatus may influence the physiology of NE poplar under unstressed conditions and upon stress. While initial physiological measurements showed no significant differences in the net CO 2 assimilation rates of both genotypes (Behnke et al, 2007(Behnke et al, , 2009(Behnke et al, , 2010a, recent observations reported lower gas exchange (Way et al, 2013) and electron transport rates (Velikova et al, 2015) in the NE genotype compared with the IE genotype.…”
Section: Whole-proteome Analysis Highlights Some Alterations In the Pmentioning
confidence: 73%
“…The lower amount of protein members of the photosynthetic apparatus may influence the physiology of NE poplar under unstressed conditions and upon stress. While initial physiological measurements showed no significant differences in the net CO 2 assimilation rates of both genotypes (Behnke et al, 2007(Behnke et al, , 2009(Behnke et al, , 2010a, recent observations reported lower gas exchange (Way et al, 2013) and electron transport rates (Velikova et al, 2015) in the NE genotype compared with the IE genotype.…”
Section: Whole-proteome Analysis Highlights Some Alterations In the Pmentioning
confidence: 73%
“…Because ETR is thylakoid membrane localized, reduced ETR in heatstressed NE plants may be explained as a consequence of altered membrane stability (Singsaas et al, 1997;Velikova et al, 2011) and/or of direct interaction of isoprene with reactive oxygen species, resulting in lower oxidative damage and lipid peroxidation (Loreto and Velikova, 2001;Velikova et al, 2005;Vickers et al, 2009). Recent findings by Velikova et al (2014Velikova et al ( , 2015 suggest that the lower ETR in NE plants may result from subcellular remodeling processes that occur in NE chloroplasts, possibly as a consequence of the RNA interference-mediated silencing of the ISPS. The analysis of the chloroplast ultrastructure, the proteome, and the lipid composition of the thylakoid membrane of IE and NE poplars (Velikova et al, , 2015 revealed a comprehensive structural and functional reorganization in the thylakoid membranes of NE plants.…”
Section: Isoprene Emission Is Not Essential For Poplar To Adapt To Famentioning
confidence: 99%
“…Recent findings by Velikova et al (2014Velikova et al ( , 2015 suggest that the lower ETR in NE plants may result from subcellular remodeling processes that occur in NE chloroplasts, possibly as a consequence of the RNA interference-mediated silencing of the ISPS. The analysis of the chloroplast ultrastructure, the proteome, and the lipid composition of the thylakoid membrane of IE and NE poplars (Velikova et al, , 2015 revealed a comprehensive structural and functional reorganization in the thylakoid membranes of NE plants. The lower amount of unsaturated fatty acids (i.e.…”
Section: Isoprene Emission Is Not Essential For Poplar To Adapt To Famentioning
confidence: 99%
“…It is also shown that isoprene stabilizes thylakoid membrane structure and its function is closely associated with structural organization and functioning of plastidial membranes (Velikova et al . , ; Pollastri et al . ).…”
Section: Introductionmentioning
confidence: 99%